2022
DOI: 10.1177/02692155221107077
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility trial of a telehealth support group intervention to reduce anxiety in multiple sclerosis

Abstract: Objective Anxiety is common among persons with MS (PwMS), but widely accepted treatments are lacking. Group-based interventions delivered via telehealth are an accessible treatment option requiring clinical trial evidence to support feasibility and initial efficacy. We conducted a pilot feasibility trial of an online support group intervention to reduce anxiety in PwMS. Methods A non-randomized, parallel arm clinical trial was conducted. A total of 31 PwMS were enrolled: 20 completed a 12-week telehealth-deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the second study [ 56 ], it was found that most participants preferred the frequency of exercise for an hour three times a week in groups of 20 to 29 people. Some studies maintained that group intervention was an effective way to promote healthy behavior [ 73 , 74 ]. The intervention process was conducive to peer support and communication, meeting the needs of interpersonal communication among elderly individuals, reducing loneliness, and promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study [ 56 ], it was found that most participants preferred the frequency of exercise for an hour three times a week in groups of 20 to 29 people. Some studies maintained that group intervention was an effective way to promote healthy behavior [ 73 , 74 ]. The intervention process was conducive to peer support and communication, meeting the needs of interpersonal communication among elderly individuals, reducing loneliness, and promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
“…While traditional methods have involved lengthy face-to-face sessions, the requirement for social distancing during the COVID-19 pandemic necessitated a wholesale pivot towards remote provision of clinical care (22). However, the potential utility of remotely applied cognitive rehabilitation in PASC is supported by precedents for this approach, with telehealth platforms having previously been used to deliver cognitive interventions in dementia (23) and MS (24). While telehealth introduces some technical and logistical considerations (25), it confers notable advantages over traditional approaches that are especially relevant for this clinical population.…”
Section: Telehealth-delivered Cognitive Rehabilitationmentioning
confidence: 99%
“…Telehealth/video conferencing group therapy and individual therapy programs have been shown to be as effective as face-to-face therapy in several studies (Gentry et al ., 2019; Poletti et al ., 2020; Scott et al ., 2022) showing support for the use of these platforms for mental health service delivery beyond COVID-19. As such, growing interest in researching telehealth-delivered interventions has been seen as a result of the pandemic in a wide range of mental health areas such as caregiver psychoeducation in schizophrenia (Mueser et al ., 2022), anxiety in multiple sclerosis (Kever et al ., 2022), clergy-delivered group therapy CBT treatments for depression (Weaver et al ., 2022) and OCD treatment for rural veterans (Fletcher et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%